The Association Between Age Groups with Clinicopathologic and Molecular Subtypes of Breast Cancer Patients - Jayadi, Tejo; Rustam, Brenda Miriane; Kristi, Puji; Dewi, Ngesti Chintia; Probowati, Wiwiek; Hariatmoko, Hariatmoko; Siagian, Jonathan Willy (Smart Medical Journal, 2022)
Introduction: The increase in incidence proportion of breast cancer disease among young patients < 40 years old is exceeding that of older patients. The purpose of the research is to know the differences between clinicopathologic and molecular subtypes between patients < 40 years old and ≥ 40 years old.Methods: The conducting research on Medical Records (MR) was an observational analytic method with a cross-sectional design. The independent variable was age. Dependent variables were histopathological type, stage of disease, grade of tumor, and molecular subtype of cancer. Univariate analyses to describe the samples. The differences between those variables according to age groups were analyzed by a bivariate statistic and the odds ratio with a confident interval (CI) of 95% of each variable would be displayed by binary logistic regression statistic. Results: The most prevalent age of breast cancer patients was in the range of 50-59 years (47%), the mean age of 53.66 ± 0.977 years, in the range of 29 years old to 86 years old, and patients aged < 40 years was 12%. Ductal carcinoma type (89.7%), stage III tumor (40.2%), poor differentiation grade III (60.7%), and luminal A subtype (42.7%) were the most prevalent clinicopathologic and molecular subtypes. There weren’t differences between histopathologic type, stage of disease, and molecular subtype with age. The histopathologic grade was different from the age variable (p=0.015). Old age had worse histopathologic differentiation than young age (OR 2.166; 95% CI 0.973-4.823).Conclusions: There weren’t significant differences between stage and molecular subtypes of breast cancer between age groups. There was poorer histopathologic differentiation in patients ≥ 40 years.